Relationship between Adequacy Level of Nutritional Intake, Hydration Status, and Work Fatigue with Employee Productivity of PT. PAL Indonesia (Persero): Hubungan Tingkat Kecukupan Asupan Zat Gizi, Status Hidrasi, dan Kelelahan Kerja dengan Produktivitas Kerja Karyawan PT. PAL Indonesia (Persero) - Salsabila Meivitama Arsanti; Farapti Farapti; Qonita Rachmah (Universitas Airlangga, 2023)
Work productivity is a comparison between the results of work in the form of goods or services with the resources or labor used in a production process. The importance of adequate nutrition for general health and work productivity requires serious attention. The purpose of this study was to determine the relationship between the level of adequacy of nutrient intake, hydration status, and level of fatigue with work productivity. This study is an analytic observational study with a cross-sectional design. The research population is the general engineering division workers of PT. PAL Indonesia (Persero). The sample size calculated using Lemeshow formula was obtained as many as 64 respondents. Primary data sourced from questionnaires and interviews with respondents as well as secondary data on work productivity. Data were analyzed using Chi-Square analysis. The results showed that there was a relationship between energy intake (p=0.010) and worker productivity. Iron intake was also associated with worker productivity (p=0.024). But there are no relationship between work productivity with hydration status (p=0.272) and level of fatigue (p=0.556). There is a relationship between energy and iron intake with work productivity, but there is no relationship between hydration status and fatigue level with work productivity. Researchers suggest for workers to consume variety of type and amount of food intake daily.